Isolation and Comparative Genomic Analysis of Reuterin-Producing Lactobacillus reuteri From the Chicken Gastrointestinal Tract - Greppi, Anna; Asare, Paul T.; Schwab, Clarissa; Zemp, Niklaus; Stephan, Roger; Lacroix, Christophe (Frontiers in Microbiology, 2020)
Lactobacillus reuteri is a natural inhabitant of selected animal and human gastrointestinal tract (GIT). Certain strains have the capacity to transform glycerol to 3-hydroxypropionaldehyde (3-HPA), further excreted to form reuterin, a potent antimicrobial system. Reuterin-producing strains may be applied as a natural antimicrobial in feed to prevent pathogen colonisation of animals, such as in chicken, and replace added antimicrobials. To date, only seven L. reuteri strains isolated from chicken have been characterised which limits phylogenetic studies and host-microbes interactions characterisation. This study aimed to isolate L. reuteri strains from chicken GIT and to characterize their reuterin production and antimicrobial resistance (AMR) profiles using phenotypic and genetic methods. Seventy strains were isolated from faces, crops and caeca of six chicken from poultry farms and samples from slaughterhouse. . Twenty-five strains were selected for further characterisation. Draft genomes were generated for the new 25 isolates and integrated into a phylogenetic tree of 40 strains from different hosts. Phylogenetic analysis based on gene content as well as on core genomes showed grouping of the selected 25 L. reuteri chicken isolates within the poultry/human lineage VI. Strains harbouring pdu-cob-cbi-hem genes (23/25) produced between 156 mM ± 11 and 330 mM ± 14 3-HPA, from 600 mM of glycerol, in the conditions of the test. All 25 chicken strains were sensitive to cefotaxime (MIC between 0.016 and 1 µg/mL) and penicillin (MIC between 0.02 and 4 µg/mL). Akin to the reference strains DSM20016 and SD2112, the novel isolates were resistant to penicillin, possibly associated with identified point mutations in ponA, pbpX, pbpF and pbpB. All strains resistant to erythromycin (4/27) carried the ermB gene, and it was only present in chicken strains. All strains resistant to tetracycline (5/27) harboured tetW gene. This study confirms the evolutionary history of poultry/human lineage VI and identifies pdu-cob-cbi-hem as a frequent trait but not always present in this lineage. L. reuteri chicken strains producing high 3-HPA yield may have potential to prevent enteropathogen colonisation of chicken.